Terminal Karawang Dengan Konsep Kontemporer - Saputra, Oki; Suryandari, Putri (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2019)
Terminal type A in Karawang is a public transport terminal that serves trips between villages, between cities within provinces and between cities between provinces. As one of the city's facilities, a contemporary concept approach with the cultural elements raised can be an added value in people's interest in using city facilities, to facilitate the local community in their activities. At present, Karawang doesn’t have a Type A Terminal to support activities, so this Terminal must be built while running a master plan for regional government. Contemporary concepts, often used by architects in designing buildings in the present. Using Charles Jencks's theory in applying Terminal design includes 3 points: ideology, variety and basic ideas. The combination of the theory of Charles Jenkcs with the cultural ideology of Karawang used, makes this building has a characteristic in terms of form, philosophy and its own meaning implied in it.